The associations between triglyceride to high-density lipoprotein cholesterol ratios and the risks of gestational diabetes mellitus and large-for-gestational-age infant - Wang, Dongyu; Xu, Shuqia; Chen, Haitian; Zhong, Lieqiang; Wang, Zilian (Clinical endocrinology (Oxford), 2015)
Summary Objective To evaluate the associations between triglyceride to high‐density lipoprotein cholesterol (TG/HDL‐C) ratios and the risks of gestational diabetes mellitus (GDM) and delivering large‐for‐gestational‐age (LGA) infant. Design This was a single‐centre prospective observational study. Patients Six hundred and thirty‐six women with a singleton pregnancy were recruited. Measurements Lipids profile, HbA1c and glucose were measured at the time of oral glucose tolerance test (OGTT) during 24–28 gestational weeks. TG/HDL‐C ratios were calculated and clinical data including perinatal parameters were analysed. Results The prevalence of GDM was 17·30% (n = 110) and LGA was 3·93% (n = 25) in this study. TG/HDL‐C ratios were found to be significantly higher in GDM group (P < 0·01) and LGA group (P = 0·045) compared with those in non‐GDM group and non‐LGA group, respectively. TG/HDL‐C ratios were independently associated with the risks of GDM (OR = 1·64, P = 0·02) and LGA (OR = 2·87, P < 0·01). The area under the combined ROC curve of TG/HDL‐C ratio and HbA1c to detect GDM was 0·705 (95% CI, 0·637–0·772). Furthermore, the area under the ROC curve of TG/HDL‐C ratio combined with HbA1c and prepregnancy BMI to detect LGA was 0·806 (95% CI, 0·719–0·893). Conclusions TG/HDL‐C ratios in combination with HbA1c and prepregnancy BMI can be good markers to predict the risks of GDM and delivering LGA infant.